REPRODUCTION, DISTRIBUTION AND HABITATS OF Chiasmocleis magnova MORAVEC AND KÖHLER, 2007 (ANURA: MICROHYLIDAE) - PÉREZ-PEÑA, Pedro E. (2022)
Chiasmocleis magnova was described with only two female individuals from the Allpahuayo Mishana National Reserve and surroundings in the Loreto region, Peru. The presence of large eggs in the holotype led the descriptors to assume that this species reproduces with direct development. After the description, records emerged to the north and south of the Amazon River; however, these records lacked photographs and most also lacked population information. This motivated us to learn more about their reproduction, distribution, and abundance by habitats. To this end, we captured and placed a pair of C. magnova in an aquaterrarium to assess their eggs and tadpoles. In parallel, we assessed bromeliads in transects in search of reproductive pairs to evaluate their oviposition. We recorded visual encounters for 460 hours in white sand forests, low hill, middle, and low terrace forests in order to estimate its abundance, and these records served as knowledge of their distribution in Loreto. Our results indicate that this species lays its eggs in bromeliads, from where small tadpoles emerge with dorsolateral eyes, a white body, and dorsal chromatophores. C. magnova is distributed in the interfluvium of the Tigre and Napo rivers, and the highest records were in the semi-deciduous azonal forest of hills of the western Amazon, which are characterized by successive and pronounced hills. This species can be found in four types of forests: on white sand, low hill, middle terrace, and low terrace forests, but it is more abundant in white sand forests. In summary, C. magnova is a species of microhylid restricted to the Tigre-Napo interfluviumwith larval development in bromeliads and greater abundance in white sand forests.